Macrophytes and their phytoremediative potential in sewage treatment plants: a literature review (Research, Society and Development, 2022)
Currently, the municipality of Belém has only 0.78% of treated sewage, noting that the capital has always had a shortage in the basic sanitation system. Given this, we can see the difficulties that exist in this sector, which is extremely important for the quality of life of society and for the environment as a whole. Therefore, this work aims to study the phytoremediative potential of macrophytes, analyzing the possibility of insertion in ETE's. The research will be developed through a literature review to consult which plants are more viable for insertion in sewage treatment plants, analyzing several relevant questions for such. Through this research, it is intended to obtain positive results that can be applied in the future in ETE's and bring benefits to the environment and society in general, in addition to providing information and clarification on the phytoremediation technique, which is being increasingly used in Brazil.